Optimization of surgical treatment of patients with hysteromyoma in reproductive period - L A Ozolinya; I A Lapina (IP Berlin A.V., 2013)
Patients of reproductive age with myomectomy often have massive adhesive process which, as a rule, results in decreased reproductive function. We have examined hemostatic and anti-adhesive activity of product Tachocomb (Nycomed as part of Takeda, Austria) which was intraoperatively administered with excision of myomatous nodes of various localization. The obtained results have allowed to make a conclusion of good efficacy and safety of the drug product